Lithium-rich lithium ferrite composite material and preparation method thereof
By reacting the heat and alkali of straw powder and alkali, the LFO/C complex of the FE-O-C key is generated, and the nitrogen-containing polymer is used to uniformly cover it to solve the stability of the existing LFO materials The problem of insufficient conductivity has achieved efficient and low -cost lithium -rich lithium -rich composite materials, and improves the performance of lithium ion batteries.
Patent Information
- Application Number
- CN202411346665.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing lithium lithium ferrate (LFO) materials have poor stability, insufficient conductivity, and uneven coating methods, resulting in limited application in lithium batteries.
By reacting the heating of straw powder and alkaline washing with the iron source and lithium source, the LFO/C complex of the FE-O-C key is generated, and the nitrogen-containing polymer is used for evenly to form a lithium iron iron-rich composite material. Essence
The good stability and conductivity of the material are realized, the production cost is reduced, and the energy density and cycle performance of the lithium -ion battery are improved.
Smart Images

Figure BDA0005061156460000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium-rich lithium ferrite composite material and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of lithium battery technology, factors that limit the capacity of lithium battery positive electrode materials have gradually surfaced. One of the main influencing factors is that during the first charging of lithium batteries, a large amount of active Li is consumed in the formation of the solid electrolyte membrane (SEI membrane) on the negative electrode surface. + , thereby reducing the battery capacity of the lithium battery.
[0003] Therefore, in order to reduce the negative impact of SEI film formation, the concept of lithium supplement additives was proposed. Currently, the commonly used lithium supplement schemes are divided into positive electrode lithium supplement and negative electrode lithium supplement. Positive electrode lithium supplement materials have the advantages of high potential, good compatibility with existing lithium battery main materials, and easy use and operation, which have attracted widespread attention. Among them, the positive electrode lithium supplement agent lithium iron oxide (LFO) has become a hot topic due to its excellent lithium supplement effect and low preparation cost, but some of its defects have also been exposed:
[0004] (1) Poor stability. LFO materials are highly active and difficult to exist stably in the air. They are easily deteriorated by reacting with CO2 and H2O, which results in their inability to function normally and poor processing performance. (2) LFO materials have poor conductivity and require a high voltage to completely remove lithium. In response to the above problems, some scholars have proposed a solution to coat the surface of LFO. However, problems such as uneven coating, enlarged particles after coating, cumbersome coating steps, and high costs still limit the application of LFO lithium supplements. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a lithium-rich lithium ferrite composite material with low cost, excellent conductive effect and good stability in the air and a preparation method thereof.
[0006] The present invention provides a method for preparing a lithium-rich lithium ferrite composite material, comprising the following steps:
[0007] S1. In an inert atmosphere, the straw powder is calcined and pyrolyzed at 400-600° C. for 30-90 min, then alkali-washed, washed, and dried to obtain pretreated straw charcoal powder;
[0008] S2, mixing the pretreated straw carbon powder and the iron source uniformly, heating to 350-500° C. in an inert atmosphere for calcination to obtain a Fe / C precursor;
[0009] S3, mixing the Fe / C precursor and the lithium source uniformly, then heating to 650-800° C. in an inert atmosphere for sintering, and crushing to obtain an LFO / C composite;
[0010] S4, mixing the LFO / C composite with a nitrogen-containing organic polymer solution with a mass fraction of 30-50wt%, heating the mixture in a water bath for reaction, and then drying and crushing the mixture to obtain a lithium-rich lithium ferrite composite material.
[0011] The present invention obtains pretreated straw carbon powder by pyrolyzing straw powder and alkali washing, wherein the straw powder is used as a raw material, and the carbon obtained by pyrolysis has a relatively high porosity and a large specific surface area, and can fix more Li ions; the alkali washing step can increase the specific surface area and the surface functional group content of the carbon, and prevent the acidic substance from remaining, thereby avoiding the lithium ions from being consumed during the secondary roasting; the pretreated straw carbon powder is then reacted with an iron source to synthesize an LFO / C composite containing Fe-OC bonds, and the carbon exposed on the surface of the LFO / C composite is used as a "base layer" to make the nitrogen-containing organic polymer more evenly coated on its surface, thereby achieving the purpose of fully isolating H2O and CO2 from contact, so that the obtained lithium-rich lithium ferrite composite material has excellent stability in the air, and the nitrogen doping therein can also improve the electronic conductivity of the material; on the other hand, the lithium-rich lithium ferrite composite material obtained by the method has a large number of Fe-OC bonds, and these Fe-OC bonds are evenly distributed inside and on the surface of the composite material, further improving the conductivity of the composite material.
[0012] Preferably, the straw powder is at least one of corn straw powder, rice straw powder, rape straw powder and wheat straw powder.
[0013] Preferably, the particle size of the straw powder is 20-100 meshes.
[0014] After the pyrolysis of S1, a process of grinding the obtained material uniformly may be further included.
[0015] Preferably, in S1, the alkali washing comprises: adding the material obtained after pyrolysis to an inorganic alkali solution with a concentration of 4 to 8 mol / L according to a solid-liquid ratio of 1:10 to 20 and stirring for 60 to 300 minutes. In the present invention, by controlling the concentration, dosage and time of the LiOH solution in the alkali washing within a certain range, the adsorption and reaction activity of the obtained pretreated straw charcoal powder can be further improved, which helps to improve the distribution uniformity of the Fe-OC bond in the material and can better improve the conductivity of the material.
[0016] Preferably, the inorganic base is at least one of LiOH, KOH and NaOH.
[0017] After the alkaline washing in S1, conventional solid-liquid separation treatment is also included, such as centrifugation and filtration.
[0018] Preferably, the washing in S1 is performed using deionized water, the purpose of which is to clean the cations on the surface of the material to avoid interference with the purity of the material; preferably, the washing conditions in S1 include: adding to deionized water and stirring for washing, repeating the washing 2 to 5 times, and the solid-liquid ratio of each repeated washing is 1:10 to 20.
[0019] After washing in S1, conventional solid-liquid separation treatment is also included, such as centrifugation and filtration.
[0020] In the present invention, the centrifugal conditions are preferably 4000 to 12000 rpm and 3 to 5 min.
[0021] Preferably, in S2, the iron source is at least one of Fe(NO3)2, FeSO4, FeSO4·7H2O, Fe2O3, and FeCl3.
[0022] Preferably, in S2, the specific method of uniformly mixing the pretreated straw charcoal powder and the iron source comprises: ball milling the pretreated straw charcoal powder and the iron source for 30 to 90 minutes at a ball-to-material ratio of 5 to 10:1 and a rotation speed of 300 to 750 rpm.
[0023] Preferably, in S2, the calcination time is 180 to 300 minutes.
[0024] Preferably, in S2, the heating rate of the calcination is 1 to 5°C / min.
[0025] Preferably, in S3, the molar ratio of Fe in the Fe / C precursor to Li in the lithium source is 1:5-6; the lithium source is at least one of LiOH, LiOH·H2O, Li2CO3, and Li2O. In the present invention, the purity of the material can be improved by controlling the Fe / Li ratio within a certain range, because a too low Fe / Li ratio will result in too high residual alkali, while a too high Fe / Li ratio will result in an increase in by-products, thereby reducing the purity of the material.
[0026] Preferably, in S3, the specific method of uniformly mixing the Fe / C precursor and the lithium source includes: ball milling the Fe / C precursor and the lithium source at a ball-to-material ratio of 5 to 10:1 and a rotation speed of 300 to 750 rpm for 30 to 90 min.
[0027] Preferably, in S3, the sintering time is 180 to 600 minutes.
[0028] Preferably, in S3, the heating rate of the sintering is 3-5°C / min.
[0029] Preferably, the particle size D50 of the LFO / C composite after pulverization is 8-15 μm. In the present invention, by controlling the particle size of the LFO / C composite within a suitable range, the consistency of the material can be improved, and the capacity fluctuation caused by large particles can be avoided, thereby improving the electrochemical performance stability of the material.
[0030] Preferably, in S4, the LFO / C compound is mixed with a nitrogen-containing organic polymer solution at a solid-liquid ratio of 1:10 to 30; the nitrogen-containing organic polymer is at least one of polyethyleneimine and melamine; and the solvent of the nitrogen-containing organic polymer solution is methanol. In the present invention, by controlling the type of nitrogen-containing organic polymer and the amount of nitrogen-containing organic polymer solution, a denser coating layer can be formed, which is conducive to better improving the air stability of the material.
[0031] Preferably, in S4, the water bath heating temperature is 50-65° C. and the time is 30-60 min. In the present invention, by controlling the water bath heating conditions within a certain range, the uniformity of the nitrogen-containing polymer coating and the compactness of the formed coating layer can be improved, which is conducive to better improving the air stability and conductivity of the material.
[0032] Preferably, in S4, the reaction is carried out under stirring at a stirring speed of 200 to 300 rpm.
[0033] After the reaction in S4 is completed, conventional solid-liquid separation treatment is also included, such as centrifugation and filtration.
[0034] Preferably, in S1 and S4, the drying step comprises: drying at 60-120° C. for 120-150 min.
[0035] Preferably, the particle size of the lithium-rich ferrite composite material after crushing is 400-600 mesh. In the present invention, by controlling the particle size of the lithium-rich ferrite composite material within a suitable range, the consistency of the material can be improved, and the capacity fluctuation caused by large particles can be avoided, thereby improving the electrochemical performance stability of the material; in addition, controlling the particles to be smaller can also effectively reduce polarization and improve Li + The transmission rate can further improve the rate performance of the material.
[0036] In the present invention, the inert atmosphere refers to an atmosphere formed by a non-reactive gas, and the non-reactive gas may be nitrogen or an inert gas such as argon or helium.
[0037] A lithium-rich lithium ferrate composite material is obtained by the preparation method.
[0038] The beneficial effects of the present invention are as follows:
[0039] The present invention first uses low-cost straw as a carbon source, reacts with an iron source to generate a Fe / C precursor with a Fe-OC bond, then mixes with a lithium source and sintered to obtain an LFO / C composite, and finally uses a nitrogen-containing organic polymer for surface coating to obtain a lithium-rich lithium ferrite composite material. On the one hand, the present invention synthesizes an LFO / C composite containing a Fe-OC bond by reacting pretreated straw carbon powder obtained after pyrolysis and alkali washing of straw powder with an iron source, and uses the carbon exposed on the surface of the LFO / C composite as a "base layer" to make the nitrogen-containing organic polymer more evenly coated on its surface, thereby achieving the purpose of fully isolating H2O and CO2 from contact, so that the obtained lithium-rich lithium ferrite composite material has excellent stability in the air, and the doping of nitrogen therein can also improve the electronic conductivity of the material; on the other hand, the lithium-rich lithium ferrite composite material obtained by the method has a large number of Fe-OC bonds, and these Fe-OC bonds are evenly distributed inside and on the surface of the composite material, further improving the conductivity of the composite material. In summary, the lithium-rich lithium iron oxide composite material obtained by the present invention has the characteristics of low production cost, excellent conductivity and good stability in the air, and its rate performance is good. + The transmission efficiency is high, and there is no particle agglomeration or overgrowth during the preparation process. It can significantly improve the energy density of lithium-ion batteries and has no obvious effect on their cycle performance, which is beneficial to improving the electrochemical properties of lithium-ion batteries. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is described in detail below through specific embodiments.
[0041] Example 1
[0042] Preparation of lithium-rich lithium iron oxide composite materials:
[0043] S1. The corn straw powder with a particle size of 40 mesh was first calcined at 500°C for 30 min in a muffle furnace under a nitrogen atmosphere, and then the obtained material was ground with a mortar for 5 min, added to a 5 mol / L LiOH solution at a solid-liquid ratio of 1:15, stirred at a speed of 400 rpm for 90 min, and then filtered. The filter residue was added to deionized water at a solid-liquid ratio of 1:15, stirred and washed for 10 min, and the washing was repeated 3 times, and then centrifuged at 8000 rpm for 3 min, and the precipitate was dried at 60°C for 120 min to obtain pretreated straw charcoal powder;
[0044] S2, 20g of pretreated straw carbon powder and 100g of Fe2O3 were placed in a ball mill, ball milled at 400rpm for 60min at a ball-to-material ratio of 5:1, and then heated to 400℃ in a nitrogen atmosphere at a heating rate of 3℃ / min for calcination for 180min to obtain a Fe / C precursor;
[0045] S3, placing 10.63g of Fe / C precursor and 10g of lithium oxide in a ball mill (the molar ratio of Fe in the Fe / C precursor to Li in the lithium oxide is 1:5.35), ball milling at 400rpm for 30min under the condition of a ball-to-material ratio of 5:1, then placing in a muffle furnace, heating to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere for sintering, the sintering time is 300min, and then crushing to a D50 of 8-15μm to obtain an LFO / C composite;
[0046] S4. The LFO / C composite was mixed with a methanol solution of polyethyleneimine having a mass fraction of 40 wt% at a solid-liquid ratio of 1:15, and the mixture was reacted by stirring at 200 rpm by heating in a water bath at 65°C for 30 min. After the reaction, the mixture was centrifuged at 8000 rpm for 3 min, and the precipitate was dried at 60°C for 120 min, and then ground to a D50 of 3-10 μm to obtain a lithium-rich lithium ferrate composite material.
[0047] Example 2
[0048] The difference between Example 2 and Example 1 is only that S1 is different, specifically as follows: S1, the rape straw powder with a particle size of 40 mesh is first roasted at 550°C for 60 min in a muffle furnace under a nitrogen atmosphere, and then the obtained material is ground with a mortar for 5 min, added to a LiOH solution with a concentration of 5 mol / L at a solid-liquid ratio of 1:17, stirred at a speed of 400 rpm for 90 min, and then filtered, and the filter residue is added to deionized water at a solid-liquid ratio of 1:15, stirred and washed for 10 min, and the washing is repeated 5 times, and then centrifuged at 8000 rpm for 3 min, and the precipitate is dried at 60°C for 120 min to obtain pretreated straw charcoal powder;
[0049] The remaining steps are consistent with S2, S3, and S4 in Example 1.
[0050] Example 3
[0051] The difference between Example 3 and Example 1 is only that S2 is different, specifically as follows: S2, 10g of pretreated straw charcoal powder and 100g of FeCl3 are placed in a ball mill, ball milled at 400rpm for 60min under a ball-to-material ratio of 5:1, and then heated to 400℃ at a heating rate of 3℃ / min in a nitrogen atmosphere for calcination, and the calcination time is 180min to obtain a Fe / C precursor;
[0052] The remaining steps are consistent with S1, S3, and S4 in Example 1.
[0053] Example 4
[0054] The only difference between Example 4 and Example 1 is that S3 is different, specifically as follows: S3, 10.17g of Fe / C precursor and 10g of lithium oxide (the molar ratio of Fe in the Fe / C precursor to Li in the lithium oxide is 1:5.17) are placed in a ball mill, ball milled at 400rpm for 30min under a ball-to-material ratio of 5:1, then placed in a muffle furnace, heated to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere for sintering, the sintering time is 300min, and then crushed to a D50 of 8-15μm to obtain an LFO / C composite;
[0055] The remaining steps are consistent with S1, S2, and S4 in Example 1.
[0056] Example 5
[0057] The only difference between Example 5 and Example 1 is that S4 is different, specifically as follows: S4, the LFO / C composite is mixed with a methanol solution of 40wt% melamine at a solid-liquid ratio of 1:15, and the mixture is reacted by stirring at 200rpm by water bath heating at 50°C for 30min. After the reaction, the mixture is centrifuged at 8000rpm for 3min, the precipitate is dried at 60°C for 120min, and then ground to a D50 of 3-10μm to obtain a lithium-rich lithium ferrate composite material.
[0058] The remaining steps are consistent with S1, S2, and S3 in Example 1.
[0059] Example 6
[0060] The only difference between Example 6 and Example 1 is that S4 is different, specifically as follows: S4, the LFO / C composite is mixed with a methanol solution of polyethyleneimine with a mass fraction of 30wt% at a solid-liquid ratio of 1:15, and the mixture is reacted by stirring at 200rpm by water bath heating. The water bath heating temperature is 60°C and the time is 60min. After the reaction is completed, centrifuge at 8000rpm for 3min, take the precipitate and dry it at 60°C for 120min, and then grind it to D50 of 3-10μm to obtain a lithium-rich lithium ferrate composite material.
[0061] The remaining steps are consistent with S1, S2, and S3 in Example 1.
[0062] Comparative Example 1
[0063] Preparation of lithium-rich lithium iron oxide composite materials:
[0064] S1. 20 g of conductive carbon black and 100 g of Fe2O3 were placed in a ball mill, and ball milled at 400 rpm for 60 min at a ball-to-material ratio of 5:1. Then, the mixture was heated to 400 °C at a heating rate of 3 °C / min in a nitrogen atmosphere for calcination for 180 min to obtain a Fe / C precursor.
[0065] S2, 10.63g of Fe / C precursor and 10g of lithium oxide were placed in a ball mill (the molar ratio of Fe in the Fe / C precursor to Li in the lithium oxide was 1:5.35), ball milled at 400rpm for 30min under a ball-to-material ratio of 5:1, then placed in a muffle furnace, heated to 650°C at a heating rate of 3°C / min in a nitrogen atmosphere for sintering, the sintering time was 300min, and then crushed to a D50 of 8-15μm to obtain an LFO / C composite;
[0066] S3. The LFO / C composite was mixed with a methanol solution of polyethyleneimine having a mass fraction of 40 wt% at a solid-liquid ratio of 1:15, and the mixture was reacted by stirring at 200 rpm by heating in a water bath at 65°C for 30 min. After the reaction, the mixture was centrifuged at 8000 rpm for 3 min, and the precipitate was dried at 60°C for 120 min, and then ground to a D50 of 3-10 μm to obtain a lithium-rich lithium ferrate composite material.
[0067] Comparative Example 2
[0068] The difference between Comparative Example 2 and Example 1 is that in S1, the corn stalk powder with a particle size of 40 mesh is first roasted in a muffle furnace at 700° C. for 120 min under a nitrogen atmosphere, and the other operations remain unchanged.
[0069] Comparative Example 3
[0070] The only difference between Comparative Example 3 and Example 1 is that S1 does not contain a washing step, which is as follows: S1, the corn straw powder with a particle size of 40 mesh is first roasted at 500°C for 30 min in a muffle furnace under a nitrogen atmosphere, and then the obtained material is ground with a mortar for 5 min, added to a 5 mol / L LiOH solution at a solid-liquid ratio of 1:15, stirred at a speed of 400 rpm for 90 min, and then filtered, and the filter residue was dried at 60°C for 120 min to obtain pretreated straw charcoal powder; the other operations remain unchanged.
[0071] Comparative Example 4
[0072] The difference between Comparative Example 4 and Example 1 is only that in S2, 50 g of pretreated straw charcoal powder and 100 g of Fe2O3 are placed in a ball mill, and the other operations remain unchanged.
[0073] Comparative Example 5
[0074] The only difference between Comparative Example 5 and Example 1 is that in S2, the temperature is raised to 700° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and the temperature is kept for 180 min for calcination, and the other operations remain unchanged.
[0075] Comparative Example 6
[0076] The difference between Comparative Example 6 and Example 1 is that in S4, the mass fraction of the methanol solution of polyethyleneimine is 10 wt %, and the other operations remain unchanged.
[0077] Comparative Example 7
[0078] The difference between Comparative Example 7 and Example 1 is that in S4, the mass fraction of the methanol solution of polyethyleneimine is 70 wt %, and the other operations remain unchanged.
[0079] Test example
[0080] The performance test of the lithium-rich lithium iron oxide composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 7 is carried out. The specific method is as follows: the obtained materials are slurried according to the ratio of lithium-rich lithium iron oxide: conductive agent: binder = 8:1:1 (mass ratio) to form a positive electrode sheet, and lithium metal is used as the negative electrode to form a button battery. The test voltage range is 2.0-4.0V. The electrochemical performance test results under different air exposure times during the button battery preparation process are shown in Table 1:
[0081] Table 1
[0082]
[0083] Among them, the air exposure time of different buckle preparation processes refers to the time the positive electrode sheet is exposed to the air after the positive electrode sheet is made.
[0084] It can be seen from the specific data of the embodiment in Table 1 that the above embodiments of the present invention achieve the following technical effects: Embodiments 1 to 7 all show relatively excellent lithium supplementation effects. Compared with Comparative Examples 1 to 6, the lithium-rich lithium ferrite composite material prepared by the present invention has excellent physical and chemical properties and obvious processing performance advantages.
[0085] By comparing Examples 1 to 2 with Comparative Example 1, it can be seen that the present invention selects the pretreated straw charcoal powder obtained by pyrolysis and alkali washing of straw powder as the carbon source, which is beneficial to improving the coating effect, increasing the LFO charge capacity, and enhancing its air stability.
[0086] By comparing Example 1 and Comparative Example 2, it can be seen that limiting the temperature and time of the carbon source pyrolysis treatment within a specific range is beneficial to significantly improve the LFO synthesis purity and enhance the conductivity.
[0087] Comparison of Examples 1 to 2 and Comparative Example 3 shows that fully cleaning the carbon source after pyrolysis and alkali washing is beneficial to reducing the impact of impurities on the purity of LFO, improving the coating effect, and enhancing the stability of LFO in the air.
[0088] Comparison of Examples 3 to 4 and Comparative Examples 4 to 5 shows that limiting the addition ratio of the carbon source and the iron source within a specific range is beneficial to improving the LFO synthesis purity, electrochemical performance and coating effect.
[0089] Comparison of Examples 5 to 6 and Comparative Examples 6 to 7 shows that limiting the concentration of the nitrogen-containing organic polymer solution within a specific range is beneficial to improving the coating effect and enhancing the air stability.
[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a lithium-rich lithium iron oxide composite material, characterized in that: The following steps are involved: S1. In an inert atmosphere, the straw powder is calcined and pyrolyzed at 400-600° C. for 30-90 min, then alkali-washed, washed, and dried to obtain pretreated straw charcoal powder; S2, mixing the pretreated straw carbon powder and the iron source in a mass ratio of 1:5-10, heating to 350-500° C. in an inert atmosphere for calcination to obtain a Fe / C precursor; S3, mixing the Fe / C precursor and the lithium source uniformly, then heating to 650-800° C. in an inert atmosphere for sintering, and crushing to obtain an LFO / C composite; S4, mixing the LFO / C composite with a nitrogen-containing organic polymer solution with a mass fraction of 30-50wt%, heating the mixture in a water bath for reaction, and then drying and crushing the mixture to obtain a lithium-rich lithium ferrite composite material.
2. The method for preparing the lithium-rich lithium iron oxide composite material according to claim 1, characterized in that: In S1, the alkali washing comprises: adding the material obtained after pyrolysis into an inorganic alkali solution with a concentration of 4 to 8 mol / L at a solid-liquid ratio of 1:10 to 20 and stirring for 60 to 300 minutes.
3. The method for preparing the lithium-rich lithium iron oxide composite material according to claim 1, characterized in that: In S3, the molar ratio of Fe in the Fe / C precursor to Li in the lithium source is 1:5-6.
4. The method for preparing the lithium-rich lithium iron oxide composite material according to claim 1, characterized in that: The particle size D50 of the LFO / C composite after pulverization is 8-15 μm.
5. The method for preparing the lithium-rich lithium iron oxide composite material according to claim 1, characterized in that: In S4, the LFO / C composite is mixed with a nitrogen-containing organic polymer solution at a solid-liquid ratio of 1:10-30; the nitrogen-containing organic polymer is at least one of polyethyleneimine and melamine.
6. The method for preparing the lithium-rich lithium iron oxide composite material according to claim 1, characterized in that: In S4, the water bath is heated at a temperature of 50 to 65° C. for 30 to 60 minutes.
7. The method for preparing the lithium-rich lithium iron oxide composite material according to claim 1, characterized in that: The particle size D50 of the lithium-rich lithium ferrite composite material after crushing is 3-10 μm.
8. A lithium-rich lithium iron oxide composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Carbon-coated lithium-rich lithium ferrite and preparation method thereof, positive electrode lithium supplementing material and application
CN117199276A
Nitrogen-doped carbon-coated anti-fluorite type lithium ferrite composite material and preparation method and application thereof in lithium supplement
CN118419901A
Positive electrode lithium supplement agent, preparation method thereof and battery
CN118507732A
Carbon-nitrogen double-layer coated positive electrode lithium supplement agent and preparation method and application thereof
CN118645629A
Ionic conductive material, core-shell structure containing the same, as well as, electrode formed therewith and metal ion battery
JP2021105140A